Adherence to Taking Medication for Pulmonary Tuberculosis Patients is Associated with Role of Medication Supervisors and Family Support - Putri, Novalya Irma; Nabela, Danvil; Safrizal, Safrizal; Anwar, Sufyan (Universitas Teuku Umar, 2023)
Tuberculosis (TB) remains a public health issue worldwide, affecting all age groups, despite being a preventable and curable disease. This study investigated the relationship between medication supervisors (RMS) and family support in medication adherence in pulmonary TB patients. This study is an observational type using a case-control design. The research was conducted in the working area of the Johan Pahlawan Community Health Center, West Aceh Regency, Aceh Province, in 2022. A total of 34 participants were recruited using the purposive sampling technique, with 17 participants in each group, i.e., the case group (non-adherent) and the control group (adherent). To minimise bias, matching was performed based on the participants' sex between the case and control groups. The chi-square test was used to test the hypothesis or to answer the research question, and the analysis was performed using computer software. The results showed that the p-value for the RMS and family support with medication adherence was <0.05, indicating a significant relationship. Thus, it can be concluded that RMS and family support significantly influence medication adherence among pulmonary TB patients.